Dėl šv. Brunono misijos šiaurinės koncepcijos - Palmaitis, Letas (Baltistica, 2009)
ON THE NORTHERN DIRECTION OF THE MISSION OF ST. BRUNO OF QUERFURT The author points to the single possibility of the “northern” (not Yatvingian, not the “southern”) direction of the mission of St. Bruno of Querfurt to Baltic Russia. This was a repetition of the previous route of St. Adalbert of Prague, of whom St. Bruno was a follower. In full correspondence with the note of Adam of Bremen on Sambians as neighbours of the Poles and Russes, the expression In confinio Rusciae et Lituae meant a boundary space between Skalvian Russes (Proto-Russians) and Lithuanian speaking tribes of the lower Neman. The author also comments on some critical remarks of his opponents.